2018
DOI: 10.1021/acssuschemeng.8b00236
|View full text |Cite
|
Sign up to set email alerts
|

Ti3+ Induced Brown TiO2 Nanotubes for High Performance Sodium-Ion Hybrid Capacitors

Abstract: Sodium-ion hybrid capacitors are attracting great attention and are emerging as promising energy storage devices, with their remarkable footsteps in energy and power densities. However, the development of efficient electrode materials that result in a minimum trade-off between their energy and power densities, and that allow long-term cycling stability, still remains a challenge for realizing their full potential as an alternate energy storage system for commercial applications. Herein, for the first time, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…Different approaches of nanostructuring TiO 2 have been employed to render it suitable for SIB application, similar to previous approaches for LIBs. Graphene‐supported TiO 2 nanospheres, graphene‐coupled TiO 2 sandwich‐like hybrids, flower‐like brown TiO 2 NTs, anatase nanoparticles, and self‐organized TiO 2 NTs have been investigated toward efficient Na‐ion storage capability. Xiong et al described the first amorphous TiO 2 anode for SIBs, and their electrodes demonstrated a reversible capacity of 150 mAh g −1 in a potential range between 2.5 and 0.9 V vs Na/Na + at 0.05 A g −1 (C/3) .…”
Section: Na‐ion Batteries With Anodically Grown Tio2 Nanotube Anodesmentioning
confidence: 99%
“…Different approaches of nanostructuring TiO 2 have been employed to render it suitable for SIB application, similar to previous approaches for LIBs. Graphene‐supported TiO 2 nanospheres, graphene‐coupled TiO 2 sandwich‐like hybrids, flower‐like brown TiO 2 NTs, anatase nanoparticles, and self‐organized TiO 2 NTs have been investigated toward efficient Na‐ion storage capability. Xiong et al described the first amorphous TiO 2 anode for SIBs, and their electrodes demonstrated a reversible capacity of 150 mAh g −1 in a potential range between 2.5 and 0.9 V vs Na/Na + at 0.05 A g −1 (C/3) .…”
Section: Na‐ion Batteries With Anodically Grown Tio2 Nanotube Anodesmentioning
confidence: 99%
“…Shaijumon and co‐workers prepared semicrystalline and crystalline anatase brown TiO 2 nanotubes (BTNT) with flower‐like structure by using hydrothermal route, as shown in Figure a . As an efficient pseudocapacitive Na + intercalation material, the as‐prepared brown TiO 2 exhibited good electrochemical performance.…”
Section: Materials For Sicsmentioning
confidence: 99%
“…b) Rate capability of SICs at different scan rates and current densities, respectively. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Materials For Sicsmentioning
confidence: 99%
“…Besides carbon materials, many transition metal oxides such as V 2 O 5 , MnO 2 , Fe 3 O 4 , MoO 2 , Nb 2 O 5 and TiO 2 . [45,56] with constructed nanostructures have been explored as pseudocapacitive anode materials, in which the disctinctive microstructures with sizable tunnels can reduce the diffusion pathways of the ions. As reported, the layer-structured V 2 O 5 with large lattice distance of 9.5 Å ((001) plane) has miscellaneous oxidation states, demonstrating obvious pseudocapacitive behavior.…”
Section: Transition Metal Oxides and Compoundsmentioning
confidence: 99%